Revision from unicompartmental to total knee replacement: The clinical outcome depends on reason for revision - Kerens, B.; Boonen, B.; Schotanus, M. G. M.; Lacroix, H.; Emans, P. J.; Kort, N. P. (The bone & joint journal, 2013)
Although it has been suggested that the outcome after revision of a unicondylar knee replacement (UKR) to total knee replacement (TKR) is better when the mechanism of failure is understood, a comparative study on this subject has not been undertaken. A total of 30 patients (30 knees) who underwent revision of their unsatisfactory UKR to TKR were included in the study: 15 patients with unexplained pain comprised group A and 15 patients with a defined cause for pain formed group B. The Oxford knee score (OKS), visual analogue scale for pain (VAS) and patient satisfaction were assessed before revision and at one year after revision, and compared between the groups. The mean OKS improved from 19 (10 to 30) to 25 (11 to 41) in group A and from 23 (11 to 45) to 38 (20 to 48) in group B. The mean VAS improved from 7.7 (5 to 10) to 5.4 (1 to 8) in group A and from 7.4 (2 to 9) to 1.7 (0 to 8) in group B. There was a statistically significant difference between the mean improvements in each group for both OKS (p = 0.022) and VAS (p = 0.002). Subgroup analysis in group A, performed in order to define a patient factor that predicts outcome of revision surgery in patients with unexplained pain, showed no pre-operative differences between both subgroups. These results may be used to inform patients about what to expect from revision surgery, highlighting that revision of UKR to TKR for unexplained pain generally results in a less favourable outcome than revision for a known cause of pain. Cite this article: Bone Joint J 2013;95-B:1204–8.